The Impact of Gas Production Decline to LPG Recovery and Optimization Strategy to Prevent LPG Facility From Shutdown - Ameria Eviany, Sutrasno Kartohardjono (International Journal of Advanced Science and Technology, 2020)
The decrease in gas from the production well is caused by two main factors, namelythe decline in formation productivity and the decrease in the production rate. The impactof the steep decline in production has resulted some risks in some operating equipment inboth offshore and onshore production facilities being over capacity, not optimum inoperation, and total shutdown in the LPG facility. To prevent this occurrence, alternativesare needed to maintain the rate of decline in production, both from the well side and fromthe equipment in the facility. Handling the production problems with right actions willreturn the producing wells with optimum capacity. In terms of equipment, for dynamicequipment such as rotating equipment, the equipment has a specific range of parametersor operating limits, thus modifications are required. Resizing the rotating equipmentincluding the control system has been assessed and selected to be the most effective andefficient method to prevent the cessation of LPG plant in producing LPG. The directimpact of restaging the rotating equipment extends the lifetime of LPG plant and alsogain some incremental of LPG recovery.